The digital advertising gap and the online news industry in Croatia - Bilić, Paško (Array, 2019)
Internet advertising brought about many changes in communication production, distribution, and consumption. By using critical political economy of communication as the mainstay of our approach, we provide supporting evidence of the ambiguous influence of data-driven advertising dynamic on the news industry and audience habits. We look at what we define as the digital advertising gap, or the difference between the size of the internet advertising market and the total income of digital news’ firms. Digital intermediaries such as Google and Facebook are the final destinations for the majority of internet advertising investments in Europe and Croatia. A multi-sided, internet advertising market creates a fertile ground for the production of untrustworthy journalistic content. The digital advertising gap provides an example of a ‘market failure’ in which the market does not efficiently allocate public information goods. We argue that the confidence in the ability of the market to self-regulate the internet should be re-considered in European and national media policies.